1965
DOI: 10.1002/cpt196566763
|View full text |Cite
|
Sign up to set email alerts
|

The “induction” of leukocyte and erythrocyte dihydrofolate reductase by methotrexate

Abstract: A study of the phenomenon of “induction” of the enzyme dihydrofolate reductase that occurs in leukocytes and erythrocytes after methotrexate administration has been made with the dog as an experimental model as weU as man. The “induction” has been shown to be specific for 4‐amino analogues of folate that are strong inhibitors of dihydrofolate reductase. Attempts to block induction with possible end products of dihydrofolate reductase activity and an inhibitor of protein synthesis, actinomycin D, were unsuccess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

1967
1967
2005
2005

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 10 publications
0
18
0
Order By: Relevance
“…Following this initial report, several in vivo and in vitro studies have shown that DHFR protein levels rapidly increase, or are "induced" in response to MTX treatment, associated with MTX bound to the protein (5)(6)(7)(8). The increase in DHFR protein levels seen upon exposure to MTX was unaffected by the transcriptional inhibitor actinomycin D but was blocked by the translational inhibitor cycloheximide indicating that this increase was not due to increased transcription (7).…”
mentioning
confidence: 99%
“…Following this initial report, several in vivo and in vitro studies have shown that DHFR protein levels rapidly increase, or are "induced" in response to MTX treatment, associated with MTX bound to the protein (5)(6)(7)(8). The increase in DHFR protein levels seen upon exposure to MTX was unaffected by the transcriptional inhibitor actinomycin D but was blocked by the translational inhibitor cycloheximide indicating that this increase was not due to increased transcription (7).…”
mentioning
confidence: 99%
“…[3',5',9-3H]MTX-Glu, (20 (17). After pelleting cellular debris by centrifugation at 10,000 g for 5 min, the remaining cell lysate was immediately applied to a 0.8 X 2.5-cm DEAE-Sephacell minicolumn equilibrated with KH2PO4 0.15 M, pH 6.2, at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…That the expanding drug-bound fraction represented DHFR was demonstrated by a corresponding increase of the enzyme activity measured by a spectrophotometric assay after drug removal from DHFR by alkaline dialysis. Increases in DHFR levels have been described previously during MTX therapy and were initially thought to result from enzyme stabilization by MTX (20), although more recent data suggest that MTX stimulates DHFR synthesis at the ribosomal level by an as yet undefined mechanism (21).…”
Section: Reversibility Of the Binding Of Mtx And Mtxpg To Dhfrmentioning
confidence: 97%
“…Bertino and co-workers (32) were the first to demonstrate that acute rises in intracellular MTX binding capacity could be a determinant ofdrug resistance in patients with acute leukemia. More recently it has been shown that in vivo resistance after MTX treatment may be due to DHFR gene amplification and elevated target enzyme levels (33-37).…”
Section: Introductionmentioning
confidence: 99%